Late Aptian long‐lived glacio‐eustatic lowstand recorded on the Arabian Plate. (18th October 2012) - Maurer, Florian; van Buchem, Frans S.P.; Eberli, Gregor P.; Pierson, Bernard J.; Raven, Madeleine J.; Larsen, Poul‐Henrik; Al‐Husseini, Moujahed I.; Vincent, Benoit
<x xml:space="preserve">Abstract</x> Terra Nova, 25, 87–94, 2013 Abstract Compelling physical evidence for a Late Aptian lowstand with an amplitude of at least 50 m is presented in subsurface seismic and core data from the Arabian Plate. Biostratigraphic dating indicates that the fall and rise bracketing this lowstand were rapid, and that the lowstand lasted for around 5 ma with distinctly cyclic sedimentation at the 0.4–0.5 ma scale (eccentricity band). A glacio‐eustatic mechanism is invoked as the most likely cause, which is supported by cooling indicated in oxygen isotope shifts and by evidence for a global expression of this lowstand from a number of locations at the mid and high latitudes. Hence, the Late Aptian data presented here document the longest Cretaceous sea‐level lowstand, interpreted as the longest cooling phase during the Cretaceous greenhouse.